DATA UCHWALENIA LEX POMPEIA DE PARRICIDIIS - Jońca, Maciej (Zeszyty Prawnicze, 2017)
The Date of Enacting lex Pompeia de parricidiis Summary Lex Pompeia de parricidiis was a statute related to a murderer of the closest relatives or patrons. It was likely to have been passed during one of the three Pompey the Great’s consulates in 70, 55 or 52 BC. Among those three options, the year 55 BC. seems the most probable. It was in the same year when Pompey took action to enact the law against luxury. Both lex Pompeia de parricidiis and rogatio sumptuaria could have constituted a part of Pompey’s major scheme meant to improve customs and restore a due respect to family in society.